Practical aspects of telehealth: are my patients suited to telehealth?. Issue 5 (14th May 2013) - Sabesan, S.; Allen, D.; Loh, P. K.; Caldwell, P.; Mozer, R.; Komesaroff, P. A.; Talman, P.; Williams, M.; Shaheen, N.; ,
Abstract: The first in a series of articles that demonstrate the practical aspects of telehealth, this paper provides three case studies that examine the suitability of telehealth for patients living in rural and remote areas who require ongoing specialist care.